Strange Bedfellows: Australia, Iran and the Dilemma of Torture‐Tainted Information Sharing. (21st November 2018) - Baldino, Daniel; Barnes, Jamal
Abstract : In the backdrop of a protracted global "war on terror" campaign, there has been a significant increase in the frequency and scope of informal intelligence‐sharing agreements by democratic states with non‐traditional partner regimes known to routinely employ torture. It will be argued that an international "norm vacuum" currently exists surrounding policies and practices in efforts to uphold the torture prohibition in these types of contemporary security relationships. This article will focus on the 2015 Australia‐Iran intelligence relationship as an illustrative case‐study to identify the problems, opportunities and risks related to such sharing arrangements and agreements. It will be argued that, at present, Australia appears indifferent to the risk of being passively complicit in torture. However, in applying an analytical framework of norm entrepreneurship, this article examines the role that countries like Australia could play in crafting normative standards and supporting appropriate behaviour about how global intelligence co‐operation should be considered through reinforcing accountability standards and the torture prohibition world‐wide.